Revisão taxonômica de Marmosops (Sciophanes) pinheiroi (Pine, 1981) (Didelphimorphia, Didelphidae) - Santos, Claudilívia Ferreira dos (2019)
The genus Marmosops Matschie, 1916 is composed of 19 valid species and presents a wide geographic distribution, occurring from Panama to southern Bolivia and southeastern Brazil. This genus comprises 19 species, although recent studies indicate that Marmosops pinheiroi (Pine, 1981) is a complex of species, requiring taxonomic revision in order to evaluate this hypothesis based on morphological and morphometric data. Therefore, the present study aims to analyze the morphological and morphometric variations of populations attributed to M. pinheiroi; delimit and characterize possible taxonomic entities recognized within the M. pinheiroi complex; define or improve the geographical distribution limits of the species recognized in this study; and describe possible new species belonging to the M. pinheiroi complex based on voucher material deposited in scientific collections. The external and craniodental morphology of 610 Marmosops specimens belonging to the “parvidens” group (except for M. pakaraimae) were examined, with M. parvidens included for comparative purposes and due to nomenclatureal relationships between this species and M. pinheiroi. Based on the existence of morphological patterns, four operational taxonomic units – OTUs were recognized. The morphometric variation patterns among OTUs were evaluated through Analysis of Variance (ANOVA), Principal Component Analysis, and Discriminant Function Analysis. The morphological and morphometric analyses confirmed that M. pinheiroi represents a complex formed by three species, namely: M. pinheiroi (stricto sensu; OTU 1), M. woodalli (OTU 2), and a species to be described (OTU 3), all of which can be distinguished by qualitative and quantitative patterns. The three species recognized herein are delimited by the Amazon and Xingu rivers. On the other hand, the Tapajós and Madeira rivers do not seem to represent geographical barriers for Marmosops sp.nov., not does the Tocantins river for M. woodalli. Finally, this study opens new perspectives for studies concerning molecular data, in order to test the hypotheses of the species recognized herein and to understand to what extent the Tapajós, Madeira and Tocantins rivers act in the isolation of Marmosops populations.